Three-tiered nodal classification system for bladder cancer: a new proposal. (February 2015) - Pedrosa, Jose A; Koch, Michael O; Kaimakliotis, Hristos Z; Monn, M Francesca; Masterson, Timothy A; Rice, Kevin R; Cary, K Clint; Foster, Richard S; Bihrle, Richard; Cheng, Liang
ABSTRACT : Aim: To evaluate a three-tiered prognostic stratification using one, two to five and >five positive lymph nodes (LNs) and this nodal staging system performs across different pelvic LN dissection (PLND) templates and adjuvant chemotherapy status.Methods: We evaluated 244 patients with positive LN urothelial cancer who underwent radical cystectomy and PLND between 2000 and 2011. Survival analyses utilizing the Kaplan-Meier method and log rank test were performed. Median follow-up was 55.3 months (range: 0.4–141). Multivariable Cox proportional hazards models were built to evaluate the prognostic stratification.Results: Extended PLND template was performed on 152 (62.3%) patients and standard on 92 (37.7%). The median number of LNs resected was 14 in the standard group vs 22 in the extended group (p < 0.01) and positive LNs was 2 vs 3 (p = 0.09), respectively. Stratification in patients with: one positive LN, two to five positive LNs or >five positive LNs lead to 5-year recurrence-free survival of: 48.6, 34.5 and 15.9% for each group, while the 5-year overall survival was: 43.0, 22.1 and 11.3%, respectively. Stratification in the three groups was also verified irrespective of PLND template and adjuvant chemotherapy. Two multivariable models confirmed the findings when controlling for demographic features and known pathologic risk factors.Conclusion: Three-tiered nodal classification system using the number of metastatic LNs (one, two to five and >five) stratifies patients with lymphatic disease into distinct prognostic groups.